Factors That Influence The E-Collaboration And Communication Tools For Knowledge Sharing In Institute Of Higher Learning: A Malaysian Perspective - Hassandoust, Farkhondeh (2010)
This study reports and examines the influencing factors on knowledge sharing through e-collaboration and communication tools available in universities such as; portal technologies, online group discussion, video and audio conference etc. The most proper technologies for online knowledge sharing from lecturerÕs viewpoint are also reported.